LIKUIDITAS, LEVERAGE, FIXED ASSETS INTENSITY, ARUS KAS OPERASI, DAN UKURAN PERUSAHAAN TERHADAP PEMILIHAN MODEL REVALUASI ASET TETAP (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017) - Fajar Gunawan; Cahyani Nuswandari (Faculty of Economic and Business Universitas STIKUBANK, 2019)
This study aims to determine the effect of liquidity, operating cash flow, leverage, fixed asset intensity, and firm size to the selection fixed asset revaluation model in manufactured companies. This research was done in Indonesia Stock Exchange (IDX) year 2013-2017.The sample in this research is taken by using purposive sampling method of 501 companies. The data usedare secondary data in the form of company's financial statements analyzed using logistic regression.The results of this study indicate that the liquidity, leverage, and operation cash flow have not effect to the selection of fixed asset revaluation model. While fixed assets intensity and firm size have positive significant effect to the selection of fixed asset revaluation model. Keywords: Fixed assets revaluation, liquidity, leverage, fixed assets intensity, operating cash flow, and firm size.